Prevalence of Dementia in China in 2015: A Nationwide Community-Based Study - Qi, Shige; Yin, Peng; Zhang, Han; Zhang, Qingjun; Xiao, Yize; Deng, Ying; Dong, Zhong; Shi, Yan; Meng, Jun; Peng, Dantao; Wang, Zhihui (Frontiers in Public Health, 2021)
Objective: The study aims to estimate the prevalence of dementia and Alzheimer’s disease (AD) and associated risk factors among the general Chinese population. Methods: We carried out a nationwide study including 24,117 participants aged 60 years and older in China by a multi-stage clustered sampling. Dementia and AD were diagnosed according to the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders and the criteria issued by the National Institute of Neurological and Communicative Disorders and Stroke–Alzheimer's Disease and Related Disorders Association. Face-to-face interviews were administered by trained interviewers to obtain information on demographics, life style factors and previous diseases. Results: The overall weighted prevalence of dementia was 4.22% (95%CI 2.27%-6.17%) for people aged 60 years and older, higher in women than in men, and increase with age. Regular tea drinking and daily exercises were protective factors for both dementia and AD. Engaging in social and intellectual activities were significantly associated with lower risk of dementia and AD. Conclusions: The large number of dementia population posed significant challenge to China where population is rapidly ageing. Increase of public awareness, building more care facilities, training dementia specialists and professional caregivers are all urgently needed and should be the future priorities of dementia care in China.